Law No. 160 of the year 2018 Amending Certain Provisions of Law No. 54/1964 on Reorganizing the Administrative Control, Social Insurance Law No. 79/1975, and Law No. 100/1987 On Determining the Financial Treatment of the President of the House of Representatives, Prime Minister, Members of the Government, Governors and Deputies Thereof = قانون رقم 160 لسنة 2018 بتعديل بعض أحكام القانون رقم 54 لسنة 1964 بإعادة تنظيم الرقابة الإدارية وتعديل بعض أحكام قانون التأمين الإجتماعى الصادر بالقانون رقم 79 لسنة 1975 وتعديل بعض أحكام القانون رقم 100 لسنة 1987 بتحديد المعاملة المالية لرئيس مجلس النواب ورئيس مجلس الوزراء وأعضاء الحكومة والمحافظين ونوابهم - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic